Treatment with convalescent plasma in solid organ transplant recipients with COVID‐19: Experience at large transplant center in New York City. Issue 12 (28th September 2020) - Rahman, Farah; Liu, Sean T. H.; Taimur, Sarah; Jacobs, Samantha; Sullivan, Timothy; Dunn, Dallas; Baneman, Emily; Fuller, Risa; Aberg, Judith A.; Bouvier, Nicole; Rana, Meenakshi M.
Abstract: Solid organ transplant (SOT) recipients may be at higher risk for poor outcomes with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection. Convalescent plasma is an investigational therapy that may benefit immunosuppressed patients by providing passive immunity. Convalescent plasma was administered to hospitalized patients with coronavirus disease‐2019 (COVID‐19) at an academic transplant center in New York City. Eligible patients were hospitalized and required to have positive nasopharyngeal polymerase chain reaction (PCR) diagnosis of SARS‐CoV‐2 infection, be at least 18 years old, and have either dyspnea, blood oxygen saturation ≤ 93% on ambient air, respiratory frequency ≥ 30 breaths/min, partial pressure of arterial oxygen to fraction of inspired oxygen ratio < 300, or lung infiltrates > 50%. Thirteen SOT recipients received convalescent plasma from April 9, 2020, to May 17, 2020. The median time from symptom onset to plasma infusion was 8 days. Eight of 13 patients (62%) had de‐escalating oxygenation support by day 7 post‐convalescent plasma. Nine (69%) patients were discharged, 1 (7%) patients remain hospitalized, and 3 (23%) patients died. This series supports the need for additional studies on convalescent plasma use in SOT recipients with COVID‐19 to better determine efficacy and identify patients who are likely to benefit.